TEACHING READING COMPREHENSION THROUGH TASK BASED LANGUAGE TEACHING - Kamba Janna Mufabar; Hilaluddin Hanafi; Aderlaepe Aderlaepe (Halu Oleo University, 2020)
This study attempted to find out: (1) Whether the Task Based Language Teaching (TBLT) affects students’ reading comprehension or not, (2) The application of task based language teaching towards students’ reading motivation. This study employed quasi experimental design to scrutinize the applicability of TBLT which involving 2nd grade students of Junior High School 7 Kendari registered in academic year 2019/2020. To this end, 62 participants (including an experimental group and a control class ones) were selected through purposive sampling from among 180 students. Task Based Language Teaching was applied in teaching reading comprehension in experimental group while in control group ones was applied conventional. Both groups were taught the same topic. The test was administered before treatment (pre-test) to examine the students’ previous reading comprehension and it was then compared with their post-test to examine their reading comprehension after being taught using TBLT. Reading test and questionnaire as the instruments of this study. The data from reading test was used to figure out the students’ reading comprehension by using t-test while the data from questionnaire was to figure out the students’ reading motivation. All collected data were computed and analysed by using SPSS 24. The results of reading comprehension test revealed that TBLT significantly effects students’ reading comprehension. Moreover, the result of questionnaire displayed that the students became more motivated to read through Task Based Language Teaching (TBLT). Keywords: Reading Comprehension, Task Based Language Teaching.